Ставлення Львівського міськкому КПРС-КПУ до реформування господарського комплексу mміста в роки перебудови (1985-1991 рр.) - Czura, Ołeksandra (Komunizm: System - Ludzie - Dokumentacja, 2015)
A key reason for systemic crisis that engulfed the economic complex of the USSR in the early 70ies of the XX century was an extremely extensive model of planned economy realization. Its ineffectiveness in market conditions proposed by restructuring at the turn of 1980-1990ies contributed to a rapid deterioration of the material conditions of the country’s citizens. All the efforts to implement cost accounting and selffinancing initiated by Communist Party leader Mikhail Gorbachov set production complex of the Soviet Union to the brink of survival. Allbranches of the state’s social and productive sector were embraced by a mrapid decline. As a result of this, the regional Communist Party elite perceived ambiguously introduction of market management methods which questioned the canons of soviet planned economy. Thus, the scientific article deals with Lviv City CPSU-CPU Committee’s Attitude to social and economic innovations that were embodied in the production environment of Lviv and their impact on the financial situation of the city’s residents.